The Influence of Platen Stiffness on a Specimen’s Failure Initiation Point and the Failure Pattern of Brittle Materials in the Standardized Uniaxial Compression Test - Diego-José Guerrero-Miguel; Martina-Inmaculada Álvarez-Fernández; Ramón Gutiérrez-Moizant; María-Belén Prendes-Gero; Celestino González-Nicieza (Mathematics, 2024)
Uniaxial compressive strength is a variable necessary for adequately characterizing a material’s mechanical properties. However, a specimen’s geometric deviations and elastic properties may lead to undesirable stress states, which cause strong discrepancies between the results of the uniaxial compression test and its theoretical foundations. While geometric deviations may cause non-uniform contact between the platen and the specimen, elastic properties can provoke severe end effects that disturb the local stress field near the points of contact. To address how the relative stiffness between the platen and the specimen influences the induced stress field, numerical simulations considering the stiffness ratios <semantics>Ep/Es=3</semantics>, <semantics>Ep/Es=1</semantics> and <semantics>Ep/Es=0.05</semantics> were performed. Subsequently, these results were employed to establish the relation between relative stiffness and specimen failure patterns in brittle materials, particularly in three different rocks. The results prove that the platen stiffness must be accurately selected to match that of the tested material, in order to avoid undesirable local stress fields near the point of contact and to induce homogeneous uniaxial compression that guarantees reliable uniaxial compressive strength characterization. Furthermore, the brittle failure patterns reported in previous studies were correlated with the induced stress fields inside the specimen depending on its platen stiffness, allowing the validity of the test results to be verified based on a simple visual inspection.